Pengaruh Latihan 3 Cone Wall Passing dan â€œVâ€ Roll To Gated Pass Terhadap Akurasi Passing Bawah - Akhmad, Noor; Suriatno, Adi (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2021)
Football is also one of the sports in West Nusa Tenggara Province which is very popular among the people. The highest achievement ever inscribed by the West Nusa Tenggara Football sport was participating in the Riau National Sports Week (PON) in 2012. The purpose of the study was to determine the effect of 3 Cone Wall Passing and "V" Roll To Gated Pass Exercises on Bottom Passing Accuracy. SSB Neo Selaparang KU 12 Players in 2021. This research uses the Experimental Design method with a one-group pretest-posttest design model. The population in this study was matched with the A-B-B-A pattern in two groups with 10 athletes each consisting of 20 players. The sampling technique used is ordinal pairing. The instrument in this study was a test of basic soccer skills. The data analysis of this research used t-test. The results showed that: the 3 cone wall passing exercise group obtained t count 6,167, the "V" roll to gated pass exercise group t calculated 4,311 and t table (df 11) 2,201 "The conclusion of this study is that there is a significant effect of 3 cone wall exercises passing on the passing accuracy of the 12-year-old SSB Neo Selaparang KU player and There is a significant effect of the â€œVâ€ roll to gated pass exercise on the accuracy of the underhand passing of the 12-year-old SSB Neo Selaparang KU player